Fuzzy State Feedback for Attitude Stabilization of Quadrotor. (13th January 2016) - Torres, Fernando; Rabhi, Abdelhamid; Lara, David; Romero, Gerardo; Pégard, Claude
In this paper, we propose an application of an algorithm, based on the T-S (Takagi-Sugeno) technique, to stabilize a quadrotor helicopter. After giving the nonlinear model of the vehicle, its representation by a T-S fuzzy model is discussed. Following this, a fuzzy controller is synthesized, which will guarantee the stability of the quadrotor. The proposed T-S controller is designed with measurable premise variables and the conditions of stability are given in terms of linear matrix inequality (LMI). Simulations and real-time experiments using a test-bed platform prove the performance of a PDC control algorithm to stabilize the vehicle robustly at a desired set point.